2019
DOI: 10.3389/fmed.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of FDG PET-CT Quantitative Parameters and Deauville-Like 5 Point-Scale in Predicting Malignancy of Focal Thyroid Incidentaloma

Abstract: Objective: To evaluate the diagnostic value of FDG PET-CT metabolic parameters and Deauville-like 5 point-scale to predict malignancy in a population of patients presenting focal thyroid incidentaloma (fTI). Design: This retrospective study included 41 fTI, classified according to cytological and histological data as benign (BL) or malignant lesion (ML). FDG PET-CT semi-quantitative parameters (SUVmax, SUVmean, SUVpeak, MTV, TLG), tumor to liver SUVmean ratio (TLRmax and TLRm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…We observed FDG SUVmax values to be significantly higher in patients with thyroid malignancies compared to patients with no thyroid malignancies, however, with an overlap in SUVmax values between benign and malignant lesions; this is in accordance with the literature where, e.g., Thuillier et al [ 22 ] reported higher SUVmax values in malignant lesions than in benign lesions, however, not significantly different. Highest SUVmax values were also found in malignant lesions in a study by Hagenimana [ 23 ], but again no SUVmax cut-off value to distinguish between benign and malignant lesions could be identified.…”
Section: Discussionsupporting
confidence: 92%
“…We observed FDG SUVmax values to be significantly higher in patients with thyroid malignancies compared to patients with no thyroid malignancies, however, with an overlap in SUVmax values between benign and malignant lesions; this is in accordance with the literature where, e.g., Thuillier et al [ 22 ] reported higher SUVmax values in malignant lesions than in benign lesions, however, not significantly different. Highest SUVmax values were also found in malignant lesions in a study by Hagenimana [ 23 ], but again no SUVmax cut-off value to distinguish between benign and malignant lesions could be identified.…”
Section: Discussionsupporting
confidence: 92%
“…There are studies on TIs reporting that MTV, TLG, or both are useful parameters in distinguishing malignant lesions from benign ones[ 27 - 31 ], while other reported different conclusions[ 32 ]. The roles of MTV and TLG in other cancers are still open to debate[ 33 - 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are promising since they confirmed most of our previous findings. Different approaches have been tested to identify [ 18 F]FDG-avid nodules at high risk of malignancy with some disappointing results, mostly lacking of any type of validation [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%